The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-15376-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling analysis on the dynamics of university students animosity towards mathematics with optimal control theory

Abstract: Animosity towards mathematics is a very common worldwide problem and it is usually caused by wrong information, low participation, low challenge tolerance, falling further behind, being unemployed, and avoiding the advanced math classes needed for success in many careers. In this study, we have considered and formulated the new SEATS compartmental mathematical model with optimal control theory to analyze the dynamics of university students’ animosity towards mathematics. We applied the next-generation matrix, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…We are interested in finding the rate of change of R 0 due to each parameter value change. e rate of change of R 0 for a change in the value of parameters h can be estimated from a normalized sensitivity index, SI (h) defined as, SI (h) � h/R 0 zR 0 /zh [21,24].…”
Section: Basic Reproduction Number Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in finding the rate of change of R 0 due to each parameter value change. e rate of change of R 0 for a change in the value of parameters h can be estimated from a normalized sensitivity index, SI (h) defined as, SI (h) � h/R 0 zR 0 /zh [21,24].…”
Section: Basic Reproduction Number Of the Modelmentioning
confidence: 99%
“…Many researchers have applied the infectious disease dynamics model to analyze violence, corruption, and other social situations. Of those researchers, some applied mathematical modeling analysis on the dynamics of university student animosity towards mathematics with optimal control theory [24], some applied modeling for the dynamics of racism in cyberspace [25], and some applied modeling for violence [26][27][28], some applied modeling for the stability analysis of corruption [29], and others study universality of political corruption networks [30]. But, to the best of our knowledge, no one has developed and analyzed a mathematical model of the di usion of violence.…”
Section: Introductionmentioning
confidence: 99%
“…A solid grasp of mathematics for communities in nations is essential for the advancement of science, technology, and economic growth. This is because mathematics skills are very widely essential in understanding other disciplines including social sciences, engineering, sciences, arts, and outspread to all areas of science, technology as well as business enterprises, and hence, it has been becoming a key in all sciences [ 37 ]. Li et al [ 38 ] formulated and analyzed a nonlinear dynamical analysis and optimal control strategies for a new rumor-spreading model with comprehensive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulation part, they examined the optimal control under 11 control strategies and through the data analysis of incremental cost-effectiveness ratio and infection averted ratio of all control strategies and provide a flexible control strategy for the security management department. Teklu and Terefe [ 37 ] formulated and analyzed a mathematical model on the dynamics of university students' with animosity towards mathematics with optimal control theory. They have shown that the animosity-free equilibrium point is local and global stability when the basic reproduction number is less than unity, and the animosity-dominance equilibrium points local and global stability whenever the basic reproduction number is greater than unity.…”
Section: Introductionmentioning
confidence: 99%
“…Formulating and analyzing a mathematical and statistical model on realworld situations in natural sciences, social sciences, engineering, arts, and business and economics disciplines plays a fundamental role in providing worthwhile tools and techniques to predict and control their future dynamics [7][8][9][10][11]. Recently, it has attracted various researchers' attention [9,12].…”
Section: Introductionmentioning
confidence: 99%